Integrated Planning for Shared Electric Vehicle System Considering Carbon Emission Reduction - Xiaohui Sun; Yumei Mi; Askar Ahtam; Zhi Zuo (World Electric Vehicle Journal)
In order to improve the operational efficiency of a shared electric vehicle (SEV) system, this paper conducts integrated planning research from the aspects of locating and sizing SEV outlets, locating and sizing charging facilities, and operation scheduling by considering the carbon emission reduction and its benefits. Firstly, a multi-objective locating model was constructed with the optimization objectives of minimum outlet construction cost and user travel time cost and minimum carbon emissions from outlet construction and vehicle routing. Secondly, a charging demand simulation predictive model framework was designed. Finally, an SEV scheduling model with maximal operating income and minimal scheduling costs as optimization objectives was constructed considering the benefits of carbon emission reduction. By applying these models to the Chicago Sketch network and using a genetic algorithm to solve the models, it is concluded that the optimal outlet location solution considering carbon emission reduction will increase the outlet construction cost and user travel time cost. When the user loss rate is 40%, the initial number of vehicles in each outlet can make the operator’s daily income reach the maximum. The number of charging piles in each outlet is optimally configured according to 55% of the highest charging demand. Scheduling can make the distribution of charging demand more uniform and reduces the maximum charging demand by about 36.8% and the total number of charging piles by about 24.0%, at the same time, increases the average time utilization rate of charging piles at all outlets by about 15.6% and the user satisfaction rate by about 8.6%. Although scheduling increases the scheduling cost by about 3.8%, it can increase the total daily revenue of operators by 6.5%. Carbon reduction benefits can increase the total daily revenue of operators by 0.7%.